3. Peran Aktor Non-Negara dalam Hubungan Internasional: Studi Kasus Human Rights Watch dalam Krisis Kemanusiaan di Myanmar - Ula, Syarifatul; Susiatiningsih, Hermini; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The conflict between Rohingya and Rakhine, make it an attractive domain for state-actor as well as non-state actors, such as Human Rights Watch (HRW). HRW was established to engage in the field of the human rights and have a duty to perform its role in the humanitarian crisis in Myanmar and has involved ethnic Rohingya Muslim. This study is initial attempt to analyse the role of HRW in the humanitarian crisis in Myanmar by using the concept of Transnational Advocacy Network (TAN). This study found that the HRW using strategy of information politics as the more dominant tactics used to carry out the role and activities. Strategies symbolic politics is also used as a campaign to get the attention and support of other interntional actors. But in practice, HRW has not succeeded in carrying out its role in leverage politics strategies, and accountability politics, because HRW too independent and not have oversight of the Myanmar government commitements related to the citizenship rights of Muslim ethnic Rohingya.